The Effects of Anti-Dumping Duties in a New Open Economy Macroeconomics Model - Chung-Fu Lai; Xi-Tsz Lee (International Journal of Economics and Financial Issues, 2016)
This paper presents New Open Economy Macroeconomics as the analytical framework in attempt to integrate the characteristics of imperfect competition market and anti-dumping behavior into a two-country (home country and foreign country) model with micro-foundation. We analyze the long-term effect of implementing antidumping duty in home country on various microeconomic variables (i.e. consumption, output, price, exchange rate, and terms of trade) when foreign country engage in dumping behaviors toward the home country. Theoretical inference and simulation analysis of this paper suggests a positive correlation between antidumping duty and domestic consumption, foreign consumption, world consumption, domestic price index, foreign price index, and exchange rate; whereas a negative correlation between antidumping duty and the domestic output, foreign output, and terms of trade. Moreover, the level of volatility in all macroeconomic variables rises when the ratio of export product price selling below its retail price in home country expands.